2017
DOI: 10.1177/2472555217701247
|View full text |Cite
|
Sign up to set email alerts
|

Study on a 3D Hydrogel-Based Culture Model for Characterizing Growth of Fibroblasts under Viral Infection and Drug Treatment

Abstract: Three-dimensional (3D) in vitro tissue models provide an approach for the systematic, repetitive, and quantitative study of drugs. In this study, we constructed an in vitro 3D acrylated hyaluronic acid (AHA) hydrogel model encapsulating fibroblasts, performed long-period 3D culture, and tested cellular topological changes and proliferation variation in the presence of herpes simplex virus-1 (HSV-1) as an infecting virus and acyclovir (ACV) as the treatment drug. The AHA hydrogels were formed by using Michael a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…To document that these organoids are amenable to infectious disease modeling, we performed infection with HSV1 and HPV16. Previous studies have applied 3-D models of fibroblasts, vaginal epithelium, and melanoma cells to study the interaction of HSV1 with epithelial cells (65,66). Yet to our knowledge a 3-D model to study HSV1 infection in oral mucosa cells has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…To document that these organoids are amenable to infectious disease modeling, we performed infection with HSV1 and HPV16. Previous studies have applied 3-D models of fibroblasts, vaginal epithelium, and melanoma cells to study the interaction of HSV1 with epithelial cells (65,66). Yet to our knowledge a 3-D model to study HSV1 infection in oral mucosa cells has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…After the tip splits completely, the inhibitor peak also divides into two peaks, and its distribution along the spatial axis k is almost the same as that of activator A ( Figure 4 c,f). Further research for the 4D biofabrication may rely on the 3D culture techniques [ 3 , 27 , 40 ] that are essentially constructing and regulating the dynamic structures composed of numerous cells.…”
Section: Tip Bifurcationmentioning
confidence: 99%
“…After the tip splits completely, the inhibitor peak also divides into two peaks, and its distribution along the spatial axis k is almost the same as that of activator A (steps 3600). Further research work for the 4D biofabrication may rely on the 3D culture techniques [3,24,25] that are essentially constructing and regulating the dynamic structures composed of numeral cells.…”
Section: Tip Bifurcationmentioning
confidence: 99%